Detection of monoclonal immunoglobulins by immunoelectrophoresis: a possible source of error. Issue 5 (May 1980) - Smith, A M; Thompson, R A; Haeney, M R
Abstract : The technique of immunoelectrophoresis (IEP) is widely employed in the qualitative analysis of serum immunoglobulins. The most commonly used support media are agarose or agar gels, but the mobility of immunoglobulins is different in these two media. The presence of a small amount of a cathodal monoclonal immunoglobulin G may not be detected on IEP in agar if it is masked by larger amounts of polyclonal immunoglobulin of the same class. In these circumstances the use of agarose imparts to the monoclonal protein a different mobility from that of the bulk of the serum IgG and allows its positive identification.